2023
DOI: 10.1159/000533429
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcome in Early-Onset Metastatic Colorectal Cancer: A Multicenter-Matched Pair Analysis

Bernhard Doleschal,
Dora Niedersüß-Beke,
Patrick Kirchweger
et al.

Abstract: <b><i>Introduction:</i></b> Survival of patients suffering from metastatic colorectal cancer (mCRC) has increased over the last decades. These benefits appear to be restricted to patients aged 50 and above. However, among the population aged &lt;50, colorectal cancer incidence and mortality rates are significantly rising. The clinical benefit of treatment in this population still is a matter of debate. We aim to compare the clinical outcome between patients aged 50 and younger. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…EO-CRC is considered an independent predictor for worse prognosis, suggesting a potentially more aggressive tumoral phenotype [ 16 , 17 ]. However, other studies have shown that there is a survival benefit for individuals with EO-CRC compared with AO-CRC, potentially due to younger patients being able to receive more aggressive treatment due to better tolerance, undergoing metastases resection more often and better ECOG scale performance as compared to patients >50 years of age who are more prone to have other comorbidities as well [ 18 ]. The aim of this study is to evaluate and compare the survival differences between metastatic early-onset colorectal cancer (mEO-CRC) and metastatic average-onset colorectal cancer (mAO-CRC) and identify associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…EO-CRC is considered an independent predictor for worse prognosis, suggesting a potentially more aggressive tumoral phenotype [ 16 , 17 ]. However, other studies have shown that there is a survival benefit for individuals with EO-CRC compared with AO-CRC, potentially due to younger patients being able to receive more aggressive treatment due to better tolerance, undergoing metastases resection more often and better ECOG scale performance as compared to patients >50 years of age who are more prone to have other comorbidities as well [ 18 ]. The aim of this study is to evaluate and compare the survival differences between metastatic early-onset colorectal cancer (mEO-CRC) and metastatic average-onset colorectal cancer (mAO-CRC) and identify associated factors.…”
Section: Introductionmentioning
confidence: 99%